2019
DOI: 10.2337/db19-1537-p
|View full text |Cite
|
Sign up to set email alerts
|

1537-P: Impact of Obesity on Outcomes of Diabetic Ketoacidosis: A Nationwide Analysis

Abstract: Background: Obesity is associated with better outcomes in diseases like myocardial infarction and heart failure, a phenomenon known as obesity paradox. However, the effect of obesity on healthcare outcomes after admission for diabetic ketoacidosis (DKA) has not been well characterized. Objective: We aimed to explore the impact of obesity and morbid obesity on outcomes in patients hospitalized with DKA. Methods: The National Inpatient Sample database for the year 2016 was queried. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Elsheikh et al, 9 reported increased mortality associated with morbid obesity in patients with DKA with an adjusted odds ratio (AOR) of 1.37 (95% CI: 1.18–1.61, but not obesity with lower BMI in the range 30–40. 9 Similarly, Mudgal et al, 10 large-scale study found that morbidly obese DKA patients had higher mortality than those without morbid obesity (0.72% vs. 0.38%; AOR = 1.85; p = 0.040). The study also reported that obese DKA patients had longer hospital stays (3.79 vs. 3.14 days, p < 0.001) than their non-obese counterparts.…”
Section: Discussionmentioning
confidence: 93%
“…Elsheikh et al, 9 reported increased mortality associated with morbid obesity in patients with DKA with an adjusted odds ratio (AOR) of 1.37 (95% CI: 1.18–1.61, but not obesity with lower BMI in the range 30–40. 9 Similarly, Mudgal et al, 10 large-scale study found that morbidly obese DKA patients had higher mortality than those without morbid obesity (0.72% vs. 0.38%; AOR = 1.85; p = 0.040). The study also reported that obese DKA patients had longer hospital stays (3.79 vs. 3.14 days, p < 0.001) than their non-obese counterparts.…”
Section: Discussionmentioning
confidence: 93%